A prevalência das doenças triadas pelo Programa Nacional de Triagem Neonatal no Estado do Pará nos anos de 2014 e 2015 - SILVA, Cleide Laranjeira da (2019)
The National Neonatal Screening Program (PNTN) has been implemented in each Brazilian state in several phases, which vary according to the diseases screened. It aims to detect diseases such as phenylketonuria that is a genetic disease, caused by a mutation in the gene that codes for the enzyme phenylalanine-hydroxylase, active in the liver and responsible for the transformation of the amino acid phenylalanine (PHE) into tyrosine; Hemoglobinopathies that result from mutations in the genes encoding the globin alpha (α) and beta (β) chains of the hemoglobin molecule. With an autosomal recessive inheritance pattern, they are the most common hereditary disorders in humans, affecting approximately 7% of the world population, and cystic fibrosis, also called Mucoviscidosis, is an autosomal recessive and chronic genetic disease with a higher prevalence in people of Caucasian origin. The target audience for screening are newborns from 0 to 30 days of age. The aim of this study is to assess the prevalence of diseases triaged by the National Neonatal Screening Program in the state of Pará in the years 2014, 2015. The present study is a retrospective, descriptive, epidemiological, quantitative analysis, with data stored in the Laboratory of Research and Diagnostic Support (LAPAD) consisting of results with laboratory diagnosis of the diseases sorted, with the following variables: sex, age, first collection event, color, origin and regional. The study is expected to identify the number of diagnosed cases of diseases triaged by the PNTN in the state of Pará. As well as mapping the regions with the highest prevalence and highlighting the variables with the highest frequency / contribution in the cases.